Principles of population genetics - Hartl, Daniel L. (Sinauer Associates, 1997)
This work gives a presentation of theory and observation for students at the undergraduate and graduate level. It introduces the principles of genetics and statistics that are relevant to population studies, and examines the forces affecting genetic variation from the molecular to the organismic level. Integrated throughout the book are descriptions of molecular and other methods used to study natural populations as well as theory using actual data. Applications of the principles discussed are illustrated by worked examples.